2014
DOI: 10.1007/s10967-014-3630-z
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of the radionuclides in groundwater of crystalline hard rock regions of central Tamil Nadu, India

Abstract: A study was conducted to understand the occurrence of the radionuclides in groundwater of crystalline hard rock region. Samples were collected to analyze major cations, anions, U, 222 Rn and stable isotopes of oxygen, hydrogen. It was inferred that few samples have U and 222 Rn concentrations higher than the permissible limit of drinking water standard. High degree of weathering of granitic rocks and long contact time of groundwater with the aquifer matrix could be the reason for enhanced U and 222 Rn levels i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Radon, which has a half-life of 3.8 days, is an inert, radioactive gas that basically originates from the decay of radium. Many studies have reported higher uranium and radon concentrations in groundwater in granitic terrains [3][4][5][6][7][8][9][10]. Higher radon concentrations are commonly detected in areas underlain by granites that usually contain more uranium than other rock types [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Radon, which has a half-life of 3.8 days, is an inert, radioactive gas that basically originates from the decay of radium. Many studies have reported higher uranium and radon concentrations in groundwater in granitic terrains [3][4][5][6][7][8][9][10]. Higher radon concentrations are commonly detected in areas underlain by granites that usually contain more uranium than other rock types [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The study area, Madurai district, is also one such complex hard-rock terrain of graphitebearing hornblende gneiss and calc-granulites. It is reported that these rock types contain higher amounts of U, in the range of 12-28 mg l -1 (Pandey and Krishnamurthy 1995;Thivya et al 2014). Though there were reports of U in the rock matrix, groundwater U data are still unavailable and no studies have been attempted so far to estimate the dissolved U and factor controlling its concentration in this region.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studied aquifers within the southern states were reported to be hard-rock aquifers in the proximity of granitic rocks ,,, and/or U mineralization zones, ,,, which likely impact the U contamination in these aquifers. However, in northwestern regions where U contamination is more prevalent, the literature is divided on the influence of basement granites.…”
Section: Resultsmentioning
confidence: 99%